2009
DOI: 10.3892/or_00000672
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CA 125 in ovarian cyst fluid of patients with epithelial ovarian cancer

Abstract: Abstract. Most ovarian tumors contain ovarian cyst fluid (oCF) which can be easily obtained during surgery. This is the first study that explored if CA 125 in oCF could be of prognostic value for patients with epithelial ovarian cancer (EOC). Of 54 patients with primary EOC, oCF and preoperative serum were collected and clinicopathological data were retrospectively obtained. CA 125 was measured with the commercially available CA 125 assay. CA 125 in oCF (n=54, median: 55,500 U/ml, range: 590-10,200,000 U/ml) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Many researchers have considered using CA-125 as a biomarker for early diagnosis [13, 14]. However, CA-125 is most of the times falsely negative infertile women with serous ovarian cancer and in Low grade serous ovarian cancer and CA-125 is positive in benign diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have considered using CA-125 as a biomarker for early diagnosis [13, 14]. However, CA-125 is most of the times falsely negative infertile women with serous ovarian cancer and in Low grade serous ovarian cancer and CA-125 is positive in benign diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusion was that the cyst fluid CA 125 cannot be used as a prognostic biomarker because only FIGO stage proved to have an independent predictive value in multivariate analysis. The study showed that the concentration of ovarian cyst fluid CA 125 in patients with mucinous tumors was significantly lower than in patients presenting with other histological types (p<0.001) and the CA 125 cyst fluid levels in patients with well-differentiated tumors was significantly lower than in patients presenting with poorly-differentiated tumors (p=0.038) (17).…”
Section: Ca 125 In the Ovarian Cyst Fluidmentioning
confidence: 81%
“…Interestingly, the two large-scale reviews [7,8] demonstrated CA125 as a prognostic factor for MCT-SCC in univariate model, but did not examine its efficacy in Cox regression model. For other ovarian cancers, it has been indicated that CA125 was a valuable predictor in univariate model but lost its significance when FIGO stage was considered in multivariate model [24,25]. So it is still controversial whether preoperative serum CA125 is an independent predictor for ovarian SCC outcome.…”
Section: Discussionmentioning
confidence: 99%